2019
DOI: 10.4049/jimmunol.1800587
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Maraviroc, an Antiretroviral Drug, Attenuates the Infiltration of T Cells into the Central Nervous System and Protects the Nigrostriatum in Hemiparkinsonian Monkeys

Abstract: Parkinson's disease (PD) is the most common neurodegenerative movement disorder in humans. Despite intense investigation, no effective therapy is available to stop the progression of this disease. It is becoming clear that both innate and adaptive immune responses are active in PD. Accordingly, we have reported a marked increase in RANTES and eotaxin, chemokines that are involved in T cell trafficking, in vivo in the substantia nigra (SN) and the serum of 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine-intoxicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Finally, toxin‐based models are often characterized by monophasic degeneration limited to dopaminergic neurons, whereas the pathology of PD is more indolent, progressive, and widespread. It is perhaps therefore not surprising that these models are associated with T cell infiltration and microglial activation that is fairly restricted to the nigrostriatal system, whereas the human disease has inflammatory foci throughout the neuraxix with Lewy pathology seen throughout the brain and with frank degeneration in non‐nigrostriatal regions such as locus coeruleus, nucleus basalis of Meynert, and the amygdala just to name a few 22 . It is interesting, however, that reducing MPTP‐induced inflammation with T cell inhibitors blocks nigrostriatal degeneration and associated motor deficits in nonhuman primates 22 …”
Section: α‐Synucleinopathies: the Use Of Toxin And α‐Synuclein‐based mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, toxin‐based models are often characterized by monophasic degeneration limited to dopaminergic neurons, whereas the pathology of PD is more indolent, progressive, and widespread. It is perhaps therefore not surprising that these models are associated with T cell infiltration and microglial activation that is fairly restricted to the nigrostriatal system, whereas the human disease has inflammatory foci throughout the neuraxix with Lewy pathology seen throughout the brain and with frank degeneration in non‐nigrostriatal regions such as locus coeruleus, nucleus basalis of Meynert, and the amygdala just to name a few 22 . It is interesting, however, that reducing MPTP‐induced inflammation with T cell inhibitors blocks nigrostriatal degeneration and associated motor deficits in nonhuman primates 22 …”
Section: α‐Synucleinopathies: the Use Of Toxin And α‐Synuclein‐based mentioning
confidence: 99%
“…22 It is interesting, however, that reducing MPTP-induced inflammation with T cell inhibitors blocks nigrostriatal degeneration and associated motor deficits in nonhuman primates. 22 The current main focus of animal models has α-synuclein at its core. α-Synuclein has been proposed to be an initiator, facilitator, and aggravator of PD pathology, 16 although it should be noted that in older individuals with PD and parkinsonism, copathologies such as tau, transactive response DNA binding protein 43 kDa (TDP-43), and amyloid, all of which are proinflammatory, have been shown to be better associated with disease progression than α-synuclein.…”
Section: ---------------------------------------------------------mentioning
confidence: 99%
“…This included reduced CCR5 in PD_R PBMC, as well as a reduction in CX3CR1 signal in PD_R memory CD4 T cells. Interestingly, CCR5 inhibitors have recently been shown to be therapeutic in a non-human primate model of PD (Mondal et al, 2019). As for CX3CR1, its potential role in PD is mainly thought to be mediated through microglia (Angelopoulou et al, 2020); however, the receptor has been shown to define T cell memory populations (Gerlach et al, 2016) which have implications in disease (Yamauchi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the adaptive immune system in the pathogenesis of PD was shown using different MPTP models. In an MPTP monkey model of PD, treatment with the antiviral oral drug Maraviroc led to a reduced infiltration of T lymphocytes into the CNS, protecting from nigrostriatum neuronal cell death and improving locomotor activities ( Mondal et al, 2019 ). Similarly, SCID, Rag1 –/– and Tcrb –/– mice, all lacking mature lymphocytes, show attenuated dopaminergic cell death following MPTP treatment, an effect abolished upon reconstitution with WT splenocytes ( Benner et al, 2008 ; Brochard et al, 2009 ).…”
Section: Parkinson’s Diseasementioning
confidence: 99%